Outcomes in non-ST-segment elevation myocardial infarction patients according to heart failure at admission: Insights from a large trial with systematic early invasive strategy. Issue 7 (20th October 2020) - Popovic, Batric; Sorbets, Emmanuel; Abtan, Jeremie; Cohen, Marc; Pollack, Charles V; Bode, Christoph; Wiviott, Stephen D; Sabatine, Marc S; Mehta, Shamir R; Ruzyllo, Witold; Rao, Sunil V; French, William J; et al.
Abstract: Background: Previous studies published before the era of systematic early invasive strategy have reported a higher mortality in non-ST-segment elevation myocardial infarction patients with heart failure. The aim of our study was to compare the clinical characteristics, outcomes and causes of death of patients according to their heart failure status at admission in a large non-ST-segment elevation myocardial infarction population with planned early invasive management. Methods: We performed a post-hoc analysis of the Treatment of Acute Coronary Syndrome with Otamixaban randomised trial which included non-ST-segment elevation myocardial infarction patients with systematic coronary angiography within 72 h. Patients were categorised according to presence or absence of heart failure (Killip grade ≥2) at admission. Results: A total of 13, 172 patients were enrolled, of whom 944 (7.2%) had heart failure. At day 30, death occurred in 213 patients (1.6%) and cardiovascular death was the dominant cause of death in both groups ((with vs without heart failure) 78.8% vs 78.4%, p  = 0.94). At six months, death occurred in 90/944 (9.5%) patients with heart failure and 258/12228 patients without heart failure (2.1%) ( p  < 0.001). After adjustment on Global Registry of Acute Coronary Events risk score, heart failure was an independent predictor of all-cause mortality at day 30 (odds ratio: 1.58; 95% confidence interval, 1.06–2.36, p  = 0.02) and at day 180 (odds ratio: 1.77; 95% confidence interval, 1.3–2.42, p  < 0.001) as well as of ischaemic complications (cardiovascular death, myocardial infarction, stent thrombosis or stroke at day 30 (odds ratio: 1.28; 95% confidence interval, 1.01–1.62, p  = 0.04). Conclusion: Non-ST-segment elevation myocardial infarction patients with heart failure at admission still have worse outcomes than those without heart failure, even with systematic early invasive strategy. Further efforts are needed to improve the prognosis of these high risk patients.